173k views
0 votes
B(1)=-54
b(n)=b(n-1) 4/3
What is the 4th term

User ViKi Vyas
by
5.5k points

2 Answers

2 votes

Answer:

-128

Explanation:

b(1) = -54

b(2) = b(1) ⋅
(4)/(3) = -72

b(3) = b(2) ⋅
(4)/(3) = -96

b(4) = b(3) ⋅
(4)/(3) = -128

User Bretton Wade
by
5.7k points
5 votes

Answer:

-128

Explanation:

Evaluate the recursive relation 3 times:

b(2)= b(1) 4/3 = (4/3)(-54) = -72

b(3) = b(2) 4/3 = (4/3)(-72) = -96

b(4) = b(3) 4/3 = (4/3)(-96) = -128

The fourth term is -128.

User Sebastian Farham
by
6.0k points